2013
DOI: 10.1111/epi.12328
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and risk of death and sudden unexpected death in the young: A nationwide study

Abstract: SUMMARYPurpose: Patients with epilepsy are at increased risk of premature death from all causes and likely also from sudden unexplained death (SUD). Many patients with epilepsy have significant comorbidity, and it is unclear how much of the increased risk can be explained by epilepsy itself. We aimed to chart the incidence of sudden unexpected death in epilepsy (SUDEP) and estimate the risk of death from all causes and SUD conferred by epilepsy independently. Methods: We conducted a historical cohort study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 26 publications
9
92
2
7
Order By: Relevance
“…Twelve Class I studies provided incidence rate data. [6][7][8][9][10][11][12][13][14][15][16][17] Imprecision in study findings resulted in moderate confidence in the evidence for SUDEP rates in childhood and low confidence in the evidence for SUDEP rates in adulthood and overall (table 1). Because of imprecision in the incidence study results with a lack of overlap of 95% confidence interval (CIs) between several comparable study populations, the guideline panel performed a randomeffects meta-analysis to provide summary measures of the absolute or relative risk of SUDEP.…”
mentioning
confidence: 99%
“…Twelve Class I studies provided incidence rate data. [6][7][8][9][10][11][12][13][14][15][16][17] Imprecision in study findings resulted in moderate confidence in the evidence for SUDEP rates in childhood and low confidence in the evidence for SUDEP rates in adulthood and overall (table 1). Because of imprecision in the incidence study results with a lack of overlap of 95% confidence interval (CIs) between several comparable study populations, the guideline panel performed a randomeffects meta-analysis to provide summary measures of the absolute or relative risk of SUDEP.…”
mentioning
confidence: 99%
“…Despite optimal medication management, about 20-30% of patients with epilepsy will continue to have more than one seizure per month, 12% will have weekly seizures, and 8% daily seizures [3,7,8]. Patients with active epilepsy have 4-5 times higher standardized mortality ratios than epilepsy patients who are seizure free, especially in the initial years after a diagnosis of epilepsy [9][10][11][12][13]. The mortality associated with epilepsy has remained stable in the last 50 years despite the introduction of multiple new anti-seizure medications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Postictal generalized EEG suppression has been considered as a possible biomarker for SUDEP (Lhatoo et al, 2010), and has been reported in all monitored SUDEP cases (Ryvlin et al, 2013). Also, postictal generalized EEG suppression occur less frequently and is significantly shorter in children compared to adults (Freitas et al, 2013) and the incidence of SUDEP is significantly lower in children (Holst et al, 2013). Nearly 40% of our patients with DS had generalized convulsive seizures followed by postictal EEG suppression.…”
Section: Termination Pattern and A Risk For Sudepmentioning
confidence: 60%